Topological differentiation of vegetation of the South Kodry-Transdnistria (Pivdennokodrynsky-Prydnistrovsky) geobotanical county (CHORNOMORSKI BOTANICAL JOURNAL, 2022)
The South Kodrynsky-Transnistria geobotanical county of downy, sessile and common oak forests and forb-grasses steppes is located on the border of the Forest-Steppe and Steppe zones. It belongs to the Danube-Moesian forest-steppe province. The area of the county covers about 625 thousand hectares. It is divided into two geobotanical districts: Pivdennokodrynsky and Pridnestrovsko-Kuchurgansky, the border between which lies along the Dniester River. The natural vegetation there is quite transformed; together with the forest plantations, it occupies about 30% of the entire county’s area, while agrocoenoses and settlements cover over 70% of the county’s area. To assess the topological differentiation of vegetation in the county that reflects its β-coenotic diversity, we compiled a complex ecological-coenotic profile. This profile demonstrates the distribution of communities that are typical for the region, particularly those having diagnostic value. Four meso-combinations reflecting the γ-coenotic diversity of the region and serving the basis of ecological-geobotanical zonality have been identified. The distinguishing feature of the county is the presence of forest with Quercus robur, Q. petraea, Q. pubescens (Carpinion betuli, Aceri tatarici-Quercion pubescentis), that are topologically displacing each other in a direction from the slopes foots to the flat interfluves. The steppe vegetation is represented there by forb-grasses communities with dominance or participation of Stipa рennata, S. tirsa, S. pulcherrima, S. capillata, Festuca valesiaca, Botriochloa ischaemum (Fragario-viridis-Trifolion montani, Festucion valesiacae). Within the region limits, the fragments of Сarex humulis communities, which are not occurring in the steppe zone of the right bank of Ukraine, are observed. At the same time, there are no Chrysopogon gryllus communities that appear on the right bank of the Dniester River. Degraded Puccinellio distantis-Juncion gerardii communities are distributed in the river floodplains. The changes of 12 evaluated leading ecological factors are reflected on the profile’s graphs. The extreme and average «background» values serving indicators for further comparison are calculated: Hd – 10.50 (mesophytic), Fh – 6.31 (hemihydrocontrastophytic), Rc – 8.58 (neutrophytic), Sl – 8.18 (eutrophic), Ca – 7.42 (acarbonathophytic), Nt – 5.95 (heminitrophytic-nitrophytic), Ae – 6.34 (hemiaerophobic), Tm – 9.10 (submesothermal), Om – 11.26 (subaridophytic), Kn – 8.62 (hemicontinental), Cr – 8.52 (hemicryophytic), Lc – 6.90 (subheliophytic). They are found to be closest to such indicators of Acero tatarici-Quercion pubescentis and Medicago-Festucetum communities. The correlation between ecological factors is established. Among them, in conditions close to the arid climate, the ombroregime and continentality of climate have a principal value. The main threats in the county are intensive plowing and fragmentation of natural communities that are sensitive to external influences. The eutrophication of forests, which is manifested by the considerable participation of nitrophilic species in their composition, is registered. As a result of climate changes and anthropogenic pressure, the forests with the domination of Quercus pubescens in the region have almost disappeared.
Keywords: vegetation, topological differentiation, Forest-Steppe zone, geobotanical county, Quercus pubescens.